Respostas

2014-05-07T17:35:47-03:00
- 4x + 8 = 10 - 6x
-4x + 6x = 10-8
2x = 2
x = 2/2
x = 1

6/5 . 10/3 = 60/15 = 4
1/3 - 1/4 = (4-3)/12 = 1/12
2/6 + 8/6 = 10/6 = 5/3
3 :- 1/2 = -6
2014-05-07T17:40:35-03:00
-4x +8 = 10 - 6x                                                     2/6 + 8/6 = 10/6  = 5/3 = 1 2/3
-4x + 6x = 10 - 8
2 x = 2                                                                  3: -1/2 = 3 .- 2/1 =  -6     
x = 2/2
x = 1

6/5.10/3=60/15 = 4

1/3 - 1/4 = mmdc=12 4/12 - 3/12 = 1/12